2014
DOI: 10.1155/2014/289803
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Glasgow Coma Scale Score with Full Outline of Unresponsiveness Scale to Predict Patients’ Traumatic Brain Injury Outcomes in Intensive Care Units

Abstract: Background. Neurological assessment is an essential element of early warning scores used to recognize critically ill patients. We compared the performance of the Glasgow Coma Scale (GCS) with Full Outline of Unresponsiveness (FOUR) scale as an alternative method in the identification of clinically relevant outcomes in traumatic brain injury. Objective. The purpose of this study was to compare the performance of GCS with FOUR scale. Methods. For this study 104 patients with brain injury were recruited from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
43
2
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 17 publications
8
43
2
4
Order By: Relevance
“…Neurological impairments are a major challenge for ICU patients and those with neurological damage. In line with other studies, the present study results indicate that FOUR is a correct predictor of mortality in ICU patients with traumatic brain injuries (1,14,19). FOUR is easy to use, and provides better information, particularly in intubated patients, and shows depth of coma in greater details compared to GCS, since it assesses brain stem reflexes and respiratory pattern (18).…”
Section: █ Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Neurological impairments are a major challenge for ICU patients and those with neurological damage. In line with other studies, the present study results indicate that FOUR is a correct predictor of mortality in ICU patients with traumatic brain injuries (1,14,19). FOUR is easy to use, and provides better information, particularly in intubated patients, and shows depth of coma in greater details compared to GCS, since it assesses brain stem reflexes and respiratory pattern (18).…”
Section: █ Resultssupporting
confidence: 90%
“…The cut-off point for FOUR was considered 6, and for GCS 5. Scores of 6 or less in FOUR and 5 or less in GCS were considered expected death-risk (14). The four score showed high reliability after translation into Persian (20).…”
Section: █ Materials and Methodsmentioning
confidence: 99%
“…Another study concluded that the FOUR score appears to be an easier tool to use and it provides a more comprehensive neurological assessment. 28 A study on pediatric patients indicated that the FOUR score is more capable than GCS in predicting the mortality and discharge of patients admitted to the PICU. 29 Another study found that the inter-rater agreement of FOUR score results was excellent among medical intensivists.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are some shortcomings of this instrument such as its inability to assess verbal response of intubated patients and its inability to assess vegetative condition of a patient experiences locked syndrome. GCS instrument does not have clinical indicators to assess the brainstem death and the changes of respiratory patterns which are used to discover the development of severity coma 10,11,15 However, there were numerous studies which have been conducted to assess the level of consciousness which have established good result for both validity and reliability scores of patients' mortality outcome in intensive care unit. Generally, this instrument is considered as simple and accessible to assess the level of consciousness.…”
Section: Discussionmentioning
confidence: 99%
“…GCS components were unable to facilitate the assessment on patients with locked syndrome. 9,10 A new instrument was made to complete the GCS instrument which still has some shortcomings, and it is called Unresponsiveness Score (FOUR score).…”
Section: Introductionmentioning
confidence: 99%